Preliminary identification of N-Acetyltransferase 2 (NAT2) gene polymorphisms in the dayak population - Dewi, Lutfiana Aswindra; Peranginangin, Jason Merari; Dewi, Lucia Vita Inandha (Surya Hijau Manfaat, 2025)
Polymorphism is a change or mutation in a gene that does not cause a change in the protein structure. The N-Acetyltransferase NAT enzyme is encoded by the N-Acetyltransferase 2 (NAT2) gene, the N-Acetyltransferase 2 (NAT2) gene, several variations of DNA known as single nucleotide polymorphisms (SNPs) that alter the genotype, haplotype, and phenotype. The NAcetyltransferase 2 (NAT2) genotype was classified into three phenotypes, namely fast acetylators, intermediate acetylators, and slow acetylators. The purpose of this study was to determine the type of polymorphism and the type of polymorphism of the NAT2 gene of the Dayak tribe. In this study, blood samples from the Dayak tribe were isolated from the Wizard Genomic DNA Purification kit and then identified Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). With stages 1. Denaturation 2. Anneling and 3. Extension using NAT2 N4 and N5 primers then RFLP with restriction enzymes KpnI, TaqI and BamHI then electrophoresed with 2% agarose gel. The results of the initial identification of the N-Acetyltransferase 2 (NAT2) gene polymorphism in the Dayak tribe obtained 5 types of genotypes NAT2*4/*5B (20%), NAT2*4/*6A (33.3%), NAT2*4/*7B (20%), NAT2*5B/5B (13.3%) and NAT2*7B/7B (13.3%). From the phenotype of the Dayak tribe, there are two medium acetylators (73.3%) and slow acetylators (26.3%).